Ubezpieczenia środowiskowe jako czynnik przyspieszania przemian prośrodowiskowych - Panasiewicz, Agnieszka (The Environmental Insurance as an Accelerating Factor in the Proenvironmental Convertions Process, 2008)
Still developing business together with the aspiration of people to aim more and more benefits give the occasion to set a number of the new impendences - particularly those are unknown till now. They can cause the different damages not only in the field of human activity but also in the personal and financial area. That is why the new instruments are implemented in all environment areas in the whole world. Among these instruments the most popular is the environmental insurance. This kind of insurance functions in a number of countries, in Poland we can say about the first phase of its development. The implementation of this kind of insurance in Poland on a wide-spread scale is inevitable.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 320-326